PAPR Analysis of OFDM using Selective Mapping Method - Nikhila, Karnakanti; Rachana, Gundapu; Bhavani, Motamarri Sai; Awaiz, Mohammad (Journal of Soft Computing Paradigm, 2022)
A common standard modulation for several high data rate wireless communication systems is Orthogonal Frequency-Division Multiplexing (OFDM). It operates by splitting up large streams of data into several parallel streams with minimal data rates. Compared to single carrier modulation systems, OFDM offers various benefits. Some of these benefits are high transmission bit rates, great spectral efficiency, and sensitivity to frequency fading channels. However, there are drawbacks with OFDM. Among the major issues is the high Peak to Average Power Ratio (PAPR), due to which the system complexity increases. The Selective Mapping approach is used in this study to lower the OFDM PAPR. In this article, simulation has been done using MATLAB, evaluated PSD, spectral efficiency, BER performance and PAPR analysis of OFDM system.
Keywords: OFDM; SLM; PAPR; BER; PSD; SNR